Reorganization of Pakistan’s Science and Technology Enterprise - Khan, M. N. (The Nucleus, 2019)
Ability of any modern society to develop and fully exploit advancements in Science and Technology (S&T) is critical to its long-term prosperity. While public investments in S&T throughout the developing world are abysmally low, what is more disturbing is the ineffective use of scarce resources. In the absence of a clear understanding of how investments in S&T enterprise improve the quality of life of citizens and enhance their security. It is not surprising that developing countries struggle to formulate and implement knowledge-driven, cost-effective, climate resilient development strategies. Changes in climate, natural disasters and increasing levels of environmental pollution are likely to aggravate the governance challenge in developing countries. This paper outlines key pillars of a reorganization strategy that aims to reenergize Pakistan’s S&T enterprise with the objective of tackling the complex array of societal challenges that changes in environment are likely to exacerbate. While S&T enterprise encompasses public and private sector institutions of higher education, research and development, the focus of this research paper is on the Ministry of Science and Technology – the federal government entity responsible for planning and management of scientific research and technology development in Pakistan. After briefly describing the history and evolution of the United States (US) S&T enterprise, the social and geopolitical context in which Pakistan has planned its past investments in science, technology and higher education is examined. The author argues, that environmental change and degradation poses a serious risk to the economic wellbeing of a state and its people. Any effective strategy aimed at mitigating and managing the adverse impacts must have it at its core the goal of building and sustaining both public and private sector institutions capable of seeking and fully exploiting relevant scientific knowledge and technology in pursuit of their respective mission.